2016
DOI: 10.1016/j.aquabot.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of warming on Potamogeton crispus growth and tissue stoichiometry in the growing season

Abstract: a b s t r a c tIncreased water temperature due to climate change may affect macrophyte phenology and nutrient content. In experimentally heated mesocosms the emergence and growth of Potamogeton crispus shoots under ambient and increased temperatures (+4.5 • C) were tracked over 55 days. At the end of the experiment we measured the C, N and P content of the P. crispus leaves. The results indicate that warming advanced the emergence of P. crispus shoots by approximately 10 days, whereas the final number of shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…Low light and high nutrient alone were found to inhibit the growth of freshwater aquatic macrophytes (Nichols and Shaw 1986;Zhang et al 2010). High-nutrient stress affects the growth of P. crispus (Zhang et al 2016). Wang et al (2013) suggested that phosphorus concentration in overlying water may be one of the factors that cause plant growth, development, and population decline of P. crispus in eutrophic waters.…”
Section: Discussionmentioning
confidence: 97%
“…Low light and high nutrient alone were found to inhibit the growth of freshwater aquatic macrophytes (Nichols and Shaw 1986;Zhang et al 2010). High-nutrient stress affects the growth of P. crispus (Zhang et al 2016). Wang et al (2013) suggested that phosphorus concentration in overlying water may be one of the factors that cause plant growth, development, and population decline of P. crispus in eutrophic waters.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, warming can advance the spring phenology of aquatic (Hansson et al., ; Velthuis, Domis et al., ; Winder & Schindler, ; Zhang et al., ) and terrestrial organisms (Parmesan, ). Indeed, we detected an advanced spring phenology and an additional delayed decrease of M. spicatum abundance under warmed conditions underlying the observed differences in M. spicatum abundance between our treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Until September, labile organic carbon (LOC) accumulated in the sediment in both treatments, as sedimentation rates were larger than decomposition rates (see Figure 2 and (Cebrian & Lartigue, 2004;Handa et al, 2014;Zhang, Hui, Luo, & Zhou, 2008). Warming can lead to shifts in carbon:nutrient ratios of aquatic plants (Ventura et al, 2008;Zhang et al, 2016), but the direction of change is not uniform across studies (Velthuis, van Deelen et al, 2017). In our experiment, aboveground plant C:N ratios were higher in the warm treatment compared to the control (Table 2), indicating a decreased quality of these plants.…”
Section: Warming Effects On Organic Carbon Burialmentioning
confidence: 99%
“…The number of studies in our analysis was rather low ( n = 3) and included a positive (Zhang et al, 2016), negative (Ventura et al, 2008), and neutral (Touchette et al, 2003) response. The different directions of responses indicate that effects of temperature on the carbon:nutrient stoichiometry of aquatic plants are not necessarily linked to the temperature increments they are exposed to.…”
Section: Discussionmentioning
confidence: 99%